Ciclosporin A inhibits production of interleukin‐12/23p40 and interleukin‐23 by the human monocyte cell line, THP‐1. (18th June 2013) - Kamata, M.; Tada, Y.; Tatsuta, A.; Kawashima, T.; Shibata, S.; Mitsui, H.; Asano, Y.; Sugaya, M.; Kadono, T.; Kanda, N.; Watanabe, S.; Sato, S.
Summary Ciclosporin (Cs)A is an effective treatment for psoriasis. However, to date, the effect of CsA on the production of interleukins (ILs) is unknown. We investigated how CsA affects production of IL‐12/23p40 and IL‐23 production by the human monocyte cell line, THP‐1, which is able to differentiate into macrophage‐like cells or normal human keratinocytes (NHKs). THP‐1 cells were preincubated with CsA, then stimulated with lipopolysaccharide (LPS), polyinosinic:polycytidylic acid or adenosine triphosphate. The levels of IL‐12/23p40 and IL‐23 released into the supernatant were assayed by ELISA. CsA significantly reduced both IL‐12/23p40 and IL‐23 production by LPS‐stimulated THP‐1 cells, but not in LPS‐stimulated macrophage‐like differentiated THP‐1 cells. None of the stimuli used significantly induced either IL‐12/23p40 or IL‐23 production in NHKs. CsA inhibits not only IL‐12/23p40 and IL‐12p70, but also heterodimeric IL‐23 production by human monocytes, which may be one possible mechanism for the therapeutic efficacy of CsA in psoriasis.